Impact of integrated yoga therapy on cognitive impairment and cardiac dysfunction in relation to quality of life in breast cancer patients undergoing chemotherapy: Study protocol for a two-arm randomized controlled trial - Inbaraj, Ganagarajan; Sathyaprabha, Talakad N.; Udupa, Kaviraja; Ram, Amritanshu; Patil, Shekar; Rajeswaran, Jamuna; Nandakumar, Krishna K.; Belur, Spoorthi; Singh, Arman Deep; Prathyusha, Parthipulli Vasuki; Bayari, Sapna K.; Raghavendra, Rao M. (Frontiers in Oncology, 2022)
Background: Chemotherapy-related cognitive impairment (CRCI) and cardiac dysfunction (CRCD) are common adverse effects seen in breast cancer patients undergoing chemotherapy. Despite the fact that these effects have a significant influence on daily functioning and overall quality of life, effective strategies to avoid and/or mitigate these adverse effects remain elusive. Yoga as a Mind-body intervention has been used increasingly by cancer patients and has undergone empirical investigations as a potential intervention for patients with cancer. Furthermore, yoga is also associated with improved cognition and cardiac functioning in healthy older adults and subjects with cognitive and cardiac impairments. Accordingly, in the current study, yoga holds promise as an intervention to prevent/manage CRCI and CRCD with improved overall QOL in women receiving chemotherapy for breast cancer. Methods: The study is a two-arm, randomized controlled trial. Women diagnosed with stage I-III breast cancer and awaiting neo-adjuvant or adjuvant chemotherapy will be recruited from a tertiary care center in Bangalore, India. Following recruitment, subjects are randomized to the intervention group (integrated yoga therapy intervention during chemotherapy) or the control group (standard care during chemotherapy). The study's primary outcome is to measure quality of life (cognitive domain) using European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). The other primary objectives will include cognitive functioning using neuropsychological test battery and cardiac autonomic function testing using heart rate variability. Secondary outcomes are Brain-derived neurotrophic factor (BDNF), brain function (functional MRI), Echocardiography, serum cortisol, Functional assessment of cancer therapy-cognition (FACT-Cog V3), perceived stress scale and Ryff Scales of Psychological Well-Being. Assessments take place before, during and after chemotherapy; 16-weeks post chemotherapy and 1-year post-baseline. Discussion: Yoga is a promising intervention for preventing and/or managing chemotherapy related adverse effects and enhancing the quality of life among breast cancer patients. The findings from this study may also help understand the protective and restorative effects of yoga and support the use of yoga prophylactically for breast cancer patients. In addition, the results of this study could help chemotherapy-exposed individuals with other solid cancer types who have cognitive and cardiac issues.